Patterned Feeding of a Hyper-Palatable Food (Oreo Cookies) Reduces Alcohol Drinking in Rats - Leon, Zoela; Shah, Krishna; Bailey, Lauren S.; Karkhanis, Anushree N.; Sirohi, Sunil (Frontiers in Behavioral Neuroscience, 2021)
While a bidirectional positive link between palatable food intake and alcohol drinking has been suggested, several rodents studies report reduced alcohol drinking following palatable diets exposure. These studies utilized purified rodents diets high in sugar/fat; however, the effects of hyper-palatable food (HPF) rich in fat and sugar on alcohol drinking remain unclear. Furthermore, neural substrates involved in HPF mediated changes in alcohol consumption are poorly understood. Therefore, the present study evaluated effects of patterned feeding of hyper-palatable food (Oreo cookies) on alcohol drinking as well as dopamine (DA) and serotonin (5-HT) content in rat’s mesocorticolimbic (medial-prefrontal cortex, orbitofrontal cortex, amygdala and nucleus accumbens) circuitry. Male Long Evans rats received 8-weeks intermittent (Mon, Tue, Wed) Oreo cookies access, which induced a patterned feeding, in which rats in the Oreo group overconsumed calories on HPF days whereas underconsumption was observed on chow only (Thu, Fri) days. Following HPF exposure, alcohol consumption was evaluated while patterned feeding continued. Alcohol intake in the Oreo group was significantly lower as compared to the chow controls. However, alcohol intake in the Oreo group increased to the levels seen in the group receiving chow following suspension of patterned HPF feeding. Finally, DA levels in the nucleus accumbens were significantly greater, whereas its metabolite (DOPAC) levels were lower in the Oreo group compared to the chow controls. Surprisingly, 5-HT levels remained unaltered in all tested brain areas. Together, these data suggest that HPF-associated increased DA availability and reduced DA turnover within mesocorticolimbic circuitry may regulate alcohol drinking following patterned HPF feeding.